In Vitro Propagation in Strawberry (Fragaria x ananassa Duch.) - Dutta, Chumki; Sen, Devyani (Indian Journal of Hill Farming, 2019)
Strawberry cultivation is a highly profitable venture producing maximum returns in short period of time. Strawberry is conventionally cultivated by runners which produce plants that are disease prone. Therefore, quality planting material is essential for successful cultivation. A major drawback of cultivation of strawberry is unavailability of runners during the cropping season. In vitro propagation of strawberry aims at mass propagation of disease free plants in a short period of time wherein use of several types of media, explants and combinations of growth regulators have been standardized for successful in vitro propagation of strawberry. This review focuses on the developments and recent advances made with reference to in vitro regeneration in strawberry